Congenital palatal fistula: Case report and review of literature - Sneha Gulati; Aditya Shivaji Yadav; Ramesh Kumar Sharma (Wolters Kluwer Medknow Publications, 2023)
Congenital palatal fistula (CPF) is the rarest phenotypic variation of cleft palate, commonly associated with submucous cleft palate (SCP). Isolated palatal fistula without SCP has been reported only rarely. We report here the case of a 4-year-old child, with a 10 mm × 5 mm CPF, presenting with nasal regurgitation and speech abnormalities. The patient had unilateral palatal muscular malposition without classical features of SCP. The repair was performed using turnover flaps and Bardach's two-long flap palatoplasty and intravelar veloplasty. Healing occurred without any complications.